Enhanced crystallization in the CsPbBr3 all-inorganic perovskite via an advanced nucleation method. Issue 9 (3rd February 2022) - Ren, Yingke; Li, Delong; Chen, Jing; Guo, Xinge; He, Chao; Li, Zhaoqian; An, Xingtao
Abstract : Organic–inorganic hybrid halide perovskites are unstable under ultraviolet (UV) irradiation. Abstract : Organic–inorganic hybrid halide perovskites are unstable under ultraviolet (UV) irradiation. To solve this profound issue, an all-inorganic CsPbBr3 perovskite device is used as the top cell to overcome the ultraviolet light instability of the FAPbI3 photovoltaic device (bottom cell). The inorganic CsPbBr3 layer is prepared via an advanced nucleation process to decrease the Gibbs free energy, resulting in more nuclei as well as a dense layer. The prepared CsPbBr3 layer acts as a UV filter to avoid the problem of UV light instability on the bottom cell. When the dense CsPbBr3 layer acts as a top cell in the 4-terminal tandem device, the FAPbI3 based bottom cell exhibits excellent stability during the UV test.